The Nature of Capitalism: How Green Can We Grow? - Mikulak, Michael (My University, 2010)
What does it mean to live sustainably? This dissertation considers the history of Western environmentalism in terms of antagonism and convergence with capitalism. Whereas many forms of environmentalism have been critical of capitalism and focused on production, contemporary forms of mainstream environmental discourses are now largely focused on reforming consumption. The dissertation considers how the greening of capitalism, as an attempt to account for the environmental crisis within the framework of neoliberalism, is interfacing with various movements focused on producing alternatives.
To this end, the dissertation focuses on alternative food movements as participating in the struggle for reimagining the current relationship between nature, culture, and the economy. Chapter One considers the significance of utilizing economic language in support of environmental reforms. It traces some dominant narratives of capitalism and nature and by utilizing discourse analysis, examines how the environmental crisis is being framed. By focusing on questions of representation, Chapter One demonstrate that conceiving ecological degradation as an economic opportunity has very profound material consequences, some of which are positive and some of which are negative.
Chapter Two contextualizes the argument by consider the politics of food, focusing in particular on the stories we tell about it, and examining how food is becoming a potent site for both resisting and reinforcing capitalist value practices. It examines the discourses of ethical consumption, pastoralism, utopia, and dystopia in a consideration of how a politics of the everyday is complicated by economic arguments.
Chapter Three moves from narrative to practice by considering how the autobiographical focus of food narratives can participate in the creation of new value systems. By focusing on the author's own experiences with the 100-Mile diet, this chapter examines the role of enchantment and technologies of self in producing forms of ecological subjectivity that can challenge capitalism.
Title: The Nature of Capitalism: How Green Can We Grow?, Author: Michael Mikulak, Location: Mills